A Contribution to Understanding Spiritual Culture of the Neolithic Communities of the Eastern Adriatic (Archaeologia Adriatica, 2022)
The paper presents a ceramic artifact found in the second half of the 20th century in Islam Grčki, in the vicinity of the Neolithic site of Graduša – Lokve. It was a stray find, presently housed in the Regional Museum in Benkovac. Decoration technique andmotifs suggest dating to the Middle Neolithic, that is the Danilo culture. Mentioned chronological and cultural framework is supported by analogies from the Adriatic region, that allow attribution of this object to the spiritual culture of the eastern Adriatic Neolithic communities.